Real clinical practice of infertility treatment in Russia: a collective opinion of 425 reproductologists - N. V. Bashmakova; E. N. Novoselova; T. A. Nazarenko; M. M. Ovchinnikova; Yu. A. Fetisova; E. V. Gergert; M. A. Ganikhina; N. G. Valiullina; E. O. Golovina; M. R. Shcherban; A. S. Semikhin; M. A. Polzikov; et al. (IRBIS LLC, 2024)
Introduction. Approaches to treatment of infertility have been progressively updated because the field of assisted reproductive technologies (ART) is a science-based symbiosis of the latest knowledge and advances in medicine, biology, and genetics. Today, a real-world clinical practice of a reproductive specialist needs to be assessed in the Russian Federation (RF) both in terms of a retrospectively analyzed development of RF in vitro fertilization (IVF) technologies and identifying promising approaches for infertility treatment in the future.Aim: analysis of current therapeutic tendencies and promising trends in real clinical practice of infertility in the Russian Federation.Materials and Methods. In 2022-2023 under the auspices of the Institute for Preventive and Social Medicine and the National Alliance for Public Health Advancement, a survey of reproductive doctors practicing at commercial and government ART centers was carried out. The questionnaire contained questions regarding describing a RF female patient's portrait with an expected ovarian reserve and response to ovarian stimulation to propose a choice of ovarian stimulation protocol as well as basic and concomitant pharmacotherapy.Results. The opinion of 425 fertility doctors from 156 ART centers in 42 cities of the Russian Federation was assessed. A portrait of a female patient with infertility in the Russian Federation was determined in accordance with the ovarian reserve, expected response to gonadotropin-based stimulation (normal response - 40 %, hyporesponse - 40 %, hyperresponse - 20 % of patients). The basic pharmacotherapy in the stimulation protocol in the IVF program based on agonists and antagonists of gonadotropinreleasing hormone (GnRH), various gonadotropin-containing drugs in female patients with expected normal, hypo- and hyperresponse to ovarian stimulation was assessed. The dominant protocol consists of using GnRH antagonist most often observed in patients with hyper- (95 % of cases), normal (75 % of cases) and hypo-response (45.5 %). Preferences in the basic and concomitant pharmacotherapy in IVF programs were identified as well as current trends in embryo transfer in fresh and cryoprotocols (a tendency to freeze all obtained embryos - "freeze-all" strategy), preimplantation genetic testing methods (used in 30 % of protocols in normal responders, 60 % in hyporesponders and 10 % in hyperresponders) were described.Conclusion. Our study provides the most large-scale analysis of the real-world clinical practice of RF reproductive specialists. A portrait of a RF female patient with infertility, expected ovarian reserve and response to ovarian stimulation was described. Contemporary approaches to select stimulation protocol, basic and concomitant pharmacotherapy in real-world clinical practice were identified. The data obtained represent an important significant cross-section for current practical approaches in real-world practice of RF fertility doctors and can serve as the basis for assessing developing ART methods in the Russian Federation as well as be used to create an evidence base for analyzing future clinical and economic effectiveness of IVF programs in the Russian Federation.